Gamescorex – A Sports Scoring Web Application for Young Sports Talents (International Journal of Scientific Research in Science and Technology, 2025)
The world of sports is rapidly evolving, demanding technological advancements that enhance scorekeeping accuracy, player visibility, and data-driven analytics. The GameScoreX Sports Scoring Web Application offers a robust, user-centric solution that bridges these gaps, especially for emerging rural sports talents. Traditional scoring systems often lack real-time tracking capabilities, multi-sport integration, and career-building features, limiting athletes and sports administrators from making informed decisions. GameScoreX is designed to revolutionize sports management by integrating live scoring, automated rule enforcement, offline accessibility, and social networking tools into a seamless, interactive platform. It caters to referees, coaches, event organizers, players, and scouts by supporting multiple sports disciplines and enabling role-based user access. This technology-driven approach not only eliminates manual errors but also enhances data consistency and engagement across local and professional sporting events GameScoreX’s cloud-based architecture ensures scalability, allowing seamless adaptation to large-scale tournaments and professional leagues. Future enhancements include wearable device integration, blockchain-based athlete verification, and AI-powered match predictions, further solidifying its role as a comprehensive sports management solution. By combining scorekeeping, athlete portfolios, and social media connectivity, GameScoreX empowers players, referees, and scouts, creating a data-driven, career-enhancing ecosystem. This innovation not only enhances gameplay visibility but also fosters community building and talent discovery, making it a transformative tool for the future of sports technology.